Phytolith Systematics
XXIV, 350 p.
Keywords: This volume is the first in theAdvances in Archaeological and Museum Science series sponsored by the Society for Archaeological Sciences. The purpose of this biennial series is to provide summaries of advances in closely defined topics in archaeometry, archaeological science, environmental archaeology, preservation technology and museum conservation. The Society for Archaeological Sciences (SAS) exists to encourage interdisci plinary collaboration between archaeologists and colleagues in the natural and physical sciences. SAS members are drawn from many disciplinary fields. However, they all share a common belief that physical science techniques and methods constitute an essential component of archaeological field and laboratory studies. The General Editors wish to express their appreciation to Renee S. Kra and Frances D. Moskovitz of Radiocarbon for their special expertise and assistance in the production of this volume. We also appreciate the contribution of the two reviewers for their excellent comments and suggestions. The General Editor responsible for undertaking the development of this volume was R. E. Taylor.